Edge-Localized Mode Control and Transport Generated by Externally Applied Magnetic Perturbations - Joseph, I. (Contributions to plasma physics (1988), 2012)
This article reviews the subject of edge localized mode (ELM) control using externally applied magnetic perturbations and proposes theoretical mechanisms that may be responsible for the induced transport changes. The first question that must be addressed is: what is the structure of magnetic field within the plasma? Although initial hypotheses focused on the possibility of the creation of a region of stochastic field lines at the tokamak edge, drift magnetohydrodynamics theory predicts that magnetic reconnection is strongly suppressed over the region of the pedestal with steep gradients and fast perpendicular rotation. Reconnection can only occur near the location where the perpendicular electron velocity vanishes, and hence the electron impedance nearly vanishes, or near the foot of the pedestal, where the plasma is sufficiently cold and resistive. The next question that must be addressed is: which processes are responsible for the observed transport changes, nonlinearity, turbulence, or stochasticity? Over the pedestal region where ions and electrons rotate in opposite directions relative to the perturbation, the quasilinear Lorentz force decelerates the electron fluid and accelerates the ion fluid. The quasilinear magnetic flutter flux is proportional to the force and produces an outward convective transport that can be significant. Over the pedestal region where the E × B flow and the electrons rotate in opposite directions relative to the perturbation, magnetic islands with a width on the order of the ion gyroradius can directly radiate drift waves. In addition, the combination of quasilinear electron transport and ion viscous transport can lead to a large net particle flux. Since there are many transport mechanisms that may be active simultaneously, it is important to determine which physical mechanisms are responsible for ELM control and to predict the scaling to future devices (© 2012 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)